Chromosomal breakpoints and changes in DNA copy number in refractory acute myeloid leukemia - El-Rifai, Wael (1997)
Comparative genomic hybridization (CGH) was used to detect changes in DNA copy number in 25 cases of refractory acute myeloid leukemia (AML). CGH detected changes in DNA copy number in nine AML (36%). Losses (82%) were more frequent than gains (18%). No high-level amplifications were detected in any of the cases. Losses involved minimal overlapping regions at 5q14q32, 7q31.2q32 and 12p12. The most frequent gain was detected at 8q. CGH gave normal results in all cases with a normal karyotype or a translocation as the sole aberration. The absence of high-level DNA copy gains suggests that, in contrast to other malignancies, gene amplification is not an important mechanism for drug resistance in AML. In addition to 5q and 7q, known to be associated with disease refractoriness, 12p may be another region related to poor prognosis.